International stock return comovements - Geert Bekaert; Robert J. Hodrick; Xiaoyan Zhang (European Central Bank (ECB), 2008)
We examine international stock return comovements using country-industry and country-style portfolios as the base portfolios. We first establish that parsimonious risk-based factor models capture the covariance structure of the data better than the popular Heston- ouwenhorst (1994) model. We then establish the following stylized facts regarding stock return comovements. First, we do not find evidence for an upward trend in return correlations, except for the European stock markets. Second, the increasing importance of industry factors relative to country factors was a short-lived, temporary phenomenon.
Keywords: C52; G11; G12; 330; APT model; Comovements; correlation dynamics; Factor models; global market integration; industry country debate; international diversification; Finanzmarkt; Kapitaleinkommen; Portfolio-Management; Industrieländer